Thermotropic super-strong adhesive

By mixing bihydroxyl ionic liquid with amino acids, guanidine derivatives or guanidine-containing polymers and heat-treated, a thermotropic super-strength adhesive suitable for different matrix and organic solvent environments is prepared, which solves the problem of insufficient thermotropic interface bonding and organic solvent tolerance in the prior art, and achieves efficient, stable and environmentally friendly bonding effects.

CN119529748APending Publication Date: 2025-02-28SHAANXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411735509.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient thermochromic interface bonding in different matrix and organic solvent environments, and the stability and tolerance of traditional adhesives in high temperatures and organic solvents are insufficient.

Method used

A thermogenic super-strong adhesive made of heat-treated by mixing bihydroxy ionic liquid with amino acids, guanidine derivatives or guanidine-containing polymers is used to achieve interfacial bonding using supramolecular combination strategy.

Benefits of technology

High-efficiency thermotropic interface bonding in different matrix and organic solvent environments is achieved, and the stability and tolerance of the adhesive in high temperature and organic solvents are significantly improved, and it is cheap and green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses a thermotropic super-strong adhesive which is a double-component adhesive prepared by taking dihydroxyl ionic liquid and amino acid or a guanidyl derivative or a guanidine-containing polymer as raw materials, mixing in a grinding or solution precipitation manner and then carrying out heat treatment, and the thermotropic super-strong adhesive is high in adhesive strength and has good tolerance to an organic solvent; the bonding strength is not obviously attenuated after long-time soaking in an organic solvent, and bonding matrixes comprise different matrixes such as stainless steel, copper, iron, zinc and aluminum. The adhesive disclosed by the invention is simple in preparation process, low in cost, green, pollution-free and degradable in raw materials, and is an adhesive meeting sustainable green and environment-friendly requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of surface interface chemistry and interface bonding, and specifically relates to an amino acid, guanidine-containing small molecule, and guanidine-containing polymer-based adhesive suitable for different matrix and organic solvent environments. A series of thermally induced super strong adhesives with excellent performance are prepared by adopting a supramolecular combination strategy. Background Art

[0002] Adhesive is a substance that can bond two or more materials together and prevent them from separating and falling off [Prog. Polym. Sci, 2021, 116: 101388]. It is widely used in aerospace, medical field, daily life, etc. Compared with physical and mechanical connections, adhesives have the advantages of flexible design, high strength-to-weight ratio, and easy manufacturing [P IMech Eng LJ Mat, 2014, 229 (5): 349-379]. The coating of adhesive requires a certain stress bearing area to provide damping and shock absorption characteristics, and can achieve interface connection of different thicknesses and different materials. Adverse factors such as electrochemical corrosion should be reduced or prevented. In order to achieve good interfacial wettability of the solid-liquid interface and thus achieve excellent bonding effect, it is usually necessary to clean the bonding interface. Interfacial bonding is a physical or chemical process that usually occurs between two substrates, and promotes strong interfacial interactions through the interfacial wettability of the adhesive on the substrate surface and its own intermolecular cohesion [Int. J. Adhes, 2024, 132: 103673]. It is well known that interfacial adhesion is very common in biological systems [Chem. Soc. Rev, 2019, 48 (10): 2682-2697], and most of its adhesion systems rely on supramolecular weak interactions to achieve the adhesion function of living systems. For example, the thousands of hair-like structures on the feet of geckos provide a large enough surface area for them to crawl freely on vertical walls only through van der Waals forces [Adv. Mater, 2020, 32 (19): 2000497]. Similar organisms, such as tubeworms and mussels, adhere to a variety of surfaces in various habitats (such as land, freshwater and ocean) by secreting proteins. This is the result of electrostatic interactions, hydrogen bonds or metal ligand complexation functions (Chem. Soc. Rev., 2016, 45, 342-358.). People have also achieved efficient adhesion of multiple interfaces through supramolecular combination strategies, artificially proving that non-covalent interactions (hydrogen bonds, van der Waals forces, electrostatic interactions, hydrophobic interactions, hydrogen bonds and steric repulsion, etc.) play a key role in the adhesive performance of adhesives (Adv. Mater., 2010, 22 (6): 729-733.). Usually, with adhesive systems such as amino acids and proteins, people consider the poor temperature tolerance of biological tissues, so the interface adhesion they pursue is mainly focused on room temperature and underwater adhesion. The interface adhesion strength of this system is usually not high, but it can fully meet the adhesion and healing of biological tissues (Adv. Mater. 2021, 33, 2102983. Adv. Funct. Mater. 2020, 30, 1901693.).From a practical point of view, amino acids, proteins, guanidine derivatives, etc. are all biocompatible substances that do not pollute or harm the environment. Therefore, if the application of these systems is extended to thermally induced interfacial bonding, in a sense, it will effectively promote the design and development of green and environmentally friendly adhesives, which will have very important practical significance in construction, electronics, cultural relics restoration, soil improvement, daily life, etc. Summary of the invention

[0003] The object of the present invention is to provide a class of thermally induced super strong adhesives suitable for different substrates and organic solvent environments.

[0004] The heat-induced super-strong adhesive provided by the present invention is prepared by uniformly mixing a dihydroxy ionic liquid with an amino acid or a guanidine derivative or a guanidine-containing polymer and then subjecting the mixture to heat treatment;

[0005] The above-mentioned dihydroxy ionic liquid is any one of the following IL1 to IL4:

[0006]

[0007] In the formula, m is an integer from 1 to 10, n is an integer from 1 to 10, and R represents Any of Represents anion.

[0008] Furthermore, the above Specifically can be selected from Cl - Br - ,I - 、NO 3 - , [PF 6 ] - , [BF 4 ] - 、[Al 2 Cl 7 ] - 、[AlCl 4 ] - ,[(CF 3 SO 2 ) 2 N] - , dioctyl sulfosuccinate ion, [CF 3 SO 3 ] - , [CF 3 COO] - Any one of .

[0009] More preferably, the amino acid is selected from any one of alanine, valine, leucine, isoleucine, methionine, aspartic acid, glutamic acid, cysteine, phenylalanine, tryptophan, lysine, histidine, glycine, threonine, tyrosine, arginine and the like.

[0010] More preferably, the guanidine derivative is selected from any one of guanidine sulfate, guanidine phosphate, phenformin, chlorhexidine, guanidine benzoic acid, guanidine propionic acid, dodecylguanidine bromide, guanidine tetrafluoroborate, and biguanidine tetrafluoroborate.

[0011] More preferably, the guanidine-containing polymer is selected from any one of polyhexamethylene biguanide hydrochloride, poly(hexamethylene dicyanoguanidine-hexamethylene diamine) hydrochloride, polyhexamethylene guanidine hydrochloride, polyhexenylguanidine, guanidine-modified chitosan, guanidine-modified polyvinyl alcohol, polyvinyl dichloride guanidine salt, guanidine polyacrylamide, lysozyme, and the like.

[0012] More preferably, the molar ratio of the dihydroxy ionic liquid to the amino acid or guanidine derivative or guanidine-containing polymer is 1:5 to 5:1.

[0013] More preferably, the heat treatment temperature is 100 to 200° C., and the heat treatment time is 10 to 60 minutes.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. The amino acid, guanidine derivative or guanidine-containing polymer used in the adhesive of the present invention is simple and sufficient in source, green and environmentally friendly, and avoids harm to the environment and human body; it is compounded with the dihydroxy ionic liquid, which itself is a viscoelastic fluid dominated by viscosity at room temperature or high temperature, has good substrate wettability and universality, and exhibits good bonding effect on various materials such as stainless steel, iron, copper, aluminum, etc.

[0016] 2. The components of the adhesive of the present invention can be stored stably for a long time. After mixing, a heat-induced adhesive material can be obtained, which usually needs to be coated on the surface of the substrate and cured after heating. The mixing preparation is relatively simple and can be prepared on demand at any time.

[0017] 3. The pretreatment temperature of the adhesive interface bonding of the present invention is 100-200° C., which breaks the temperature range of the thermal treatment of supramolecular adhesives, especially adhesives containing guanidine protein, and is no longer limited to room temperature.

[0018] 4. The adhesives of the present invention are all in a fluid state, have good interface wettability, and have good ultra-low temperature tolerance. They can maintain good stability at extremely low temperatures, and their bonding strength has no obvious attenuation; and they can tolerate organic solvents. The samples bonded by them have no obvious attenuation in bonding strength after long-term immersion in various organic solvents such as ethanol, ethyl acetate, acetone, acetonitrile, petroleum ether, anhydrous ether, and dichloromethane. They can be loaded with heavy objects and immersed for several months without falling off. The interface bonding in the organic solvent system has potential application value.

[0019] 5. The adhesive of the present invention can achieve effective interface adhesion on substrates of different materials, and the adhesive is low-cost, biodegradable, green and environmentally friendly, and meets the needs of the times. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 : is the temperature scanning diagram of adhesive P1 in Example 1.

[0021] Figure 2 is the thermogravimetric analysis chart of the adhesive P1 in Example 1.

[0022] Figure 3 : is the temperature scanning diagram of adhesive P2 in Example 2.

[0023] Figure 4 is the thermogravimetric analysis diagram of adhesive P2 in Example 2.

[0024] Figure 5 This is the temperature scan diagram of adhesive P3 in Example 3.

[0025] Figure 6 is the thermogravimetric analysis diagram of adhesive P3 in Example 3.

[0026] Figure 7 : is the temperature scanning diagram of adhesive P4 in Example 4.

[0027] Figure 8 This is the thermogravimetric analysis diagram of adhesive P4 in Example 4.

[0028] Fig. 9 : is the temperature scanning diagram of the adhesive PA in Example 5.

[0029] Fig.10 is the thermogravimetric analysis chart of the adhesive PA in Example 5.

[0030] Fig.11 This is the temperature scan diagram of the adhesive PB in Example 6.

[0031] Fig.12 This is the thermogravimetric analysis diagram of the adhesive PB in Example 6.

[0032] Fig.13: is the temperature scanning diagram of the adhesive PC in Example 7.

[0033] Fig.14 This is the thermogravimetric analysis chart of the adhesive PC in Example 7.

[0034] Fig.15 : is the temperature scanning diagram of the adhesive PD in Example 8.

[0035] Fig.16 is a thermogravimetric analysis chart of the adhesive PD in Example 8.

[0036] Fig.17 It is the bonding strength of the adhesive made from the basic amino acid and the dihydroxy ionic liquid IL1-1 in Example 9.

[0037] Fig.18 It is the bonding strength of the adhesive made from the acidic amino acid and the dihydroxy ionic liquid IL1-1 in Example 9.

[0038] Fig.19 It is the bonding strength of the adhesive made from the neutral amino acid and the dihydroxy ionic liquid IL1-1 in Example 9.

[0039] Fig. 20 It is the bonding strength of the adhesive made of non-polar amino acid and dihydroxy ionic liquid IL1-1 in Example 9.

[0040] Fig.21 is the bonding strength of the adhesive made from the three guanidine-containing polymers and the dihydroxy ionic liquid IL1-1 in Example 10. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0042] The structural formula of the dihydroxy ionic liquid used in the following examples is:

[0043]

[0044] Example 1

[0045] 0.1191 g (0.22 mmol) of dihydroxy ionic liquid IL1-1 and 0.1149 g (0.66 mmol) of arginine were ground and mixed to obtain adhesive P1. The adhesive was drop-coated on the substrate surface, preheated at 200°C for 20 minutes, taken out, cured at room temperature, and the bonding properties were measured.

[0046] Example 2

[0047] 0.0802 g (0.22 mmol) of dihydroxy ionic liquid IL2-1 and 0.1149 g (0.66 mmol) of arginine were ground and mixed to obtain adhesive P2. The adhesive was drop-coated on the substrate surface, preheated at 200°C for 20 minutes, taken out, cured at room temperature, and the bonding properties were measured.

[0048] Example 3

[0049] 0.1293 g (0.22 mmol) of dihydroxy ionic liquid IL3-1 and 0.1149 g (0.66 mmol) of arginine were ground and mixed to obtain adhesive P3. The adhesive was drop-coated on the substrate surface, preheated at 200° C. for 20 minutes, taken out, cured at room temperature, and the bonding properties were measured.

[0050] Depend on Figures 1 to 6 It can be seen that when the temperature is low, the storage modulus (G') of adhesives P1 to P3 is greater than the loss modulus (G"), and the morphology is dominated by elasticity; when the temperature exceeds 80°C, the loss modulus (G") begins to be greater than the storage modulus (G'), and the morphology of adhesives P1 to P3 is dominated by viscosity; this indicates that heating will cause adhesives P1 to P3 to gradually transform into viscoelastic fluids dominated by viscosity. Moreover, as the temperature increases, both the storage modulus (G') and the loss modulus (G") decrease, showing temperature dependence. Moreover, the mass of adhesives P1 to P3 will experience the first significant decrease at 45 to 65°C, and adhesives P1 to P3 will rapidly decompose at 215 to 225°C, with the mass dropping to about 20%.

[0051] Example 4

[0052] 0.0862 g (0.22 mmol) of dihydroxy ionic liquid IL4-1 and 0.1149 g (0.66 mmol) of arginine were ground and mixed to obtain adhesive P4. The adhesive was drop-coated on the substrate surface, preheated at 200° C. for 20 minutes, taken out, cured at room temperature, and the bonding properties were measured.

[0053] Depend on Figure 7 It can be seen that the storage modulus (G') of adhesive P4 is always greater than the loss modulus (G"), is dominated by elasticity, and shows temperature dependence. Figure 8 It can be seen that the quality of adhesive P4 will first decrease significantly at 45-65°C, and the adhesive P4 will decompose rapidly at 215-225°C, and the quality will decrease to about 20%.

[0054] Example 5

[0055] 0.0500 g of dihydroxy ionic liquid IL1-1 (0.087 mmol) and 0.1500 g (0.052 mmol) of lysozyme were ground and mixed. After mixing evenly, the adhesive PA was obtained and drop-coated on the surface of the substrate. After preheating at 200° C. for 20 minutes, the adhesive was taken out and cured at room temperature, and the bonding properties were measured.

[0056] Example 6

[0057] 0.0500 g of dihydroxy ionic liquid IL2-1 (0.14 mmol) and 0.1500 g (0.052 mmol) of lysozyme (molar number) were ground and mixed to obtain adhesive PB, which was drop-coated on the surface of the substrate, preheated at 200°C for 20 minutes, taken out, cured at room temperature, and the bonding properties were measured.

[0058] Example 7

[0059] 0.0500 g of dihydroxy ionic liquid IL3-1 (0.085 mmol) and 0.1500 g (0.052 mmol) of lysozyme were ground and mixed, and the adhesive PC was obtained after being evenly mixed. The adhesive PC was drop-coated on the surface of the substrate, preheated at 200° C. for 20 minutes, taken out, cured at room temperature, and the bonding properties were measured.

[0060] Example 8

[0061] 0.0500 g of dihydroxy ionic liquid IL4-1 (0.14 mmol) and 0.1500 g (0.052 mmol) of lysozyme were ground and mixed, and the adhesive PD was obtained after being mixed evenly. The adhesive was drop-coated on the surface of the substrate, preheated at 200° C. for 20 minutes, taken out, cured at room temperature, and the bonding properties were measured.

[0062] Depend on Figures 9 to 16 It can be seen that the storage modulus (G') of the adhesives PA~PD is always greater than the loss modulus (G"), and the morphology is dominated by elasticity. Moreover, with the increase of temperature, both the storage modulus (G') and the loss modulus (G") decrease. When the temperature exceeds 160°C, both the storage modulus (G') and the loss modulus (G") rebound, showing temperature dependence. The mass of the adhesives PA~PD will undergo the first significant decrease at 45-75°C, and the adhesive PA will decompose rapidly at 192-200°C, and the mass will drop to about 20%.

[0063] Example 9

[0064] The dihydroxy ionic liquid IL1-1 was ground and mixed with basic amino acids (D-arginine, Arg; L-lysine, Lys; D-histidine, His), acidic amino acids (L-aspartic acid, Asp; D-glutamic acid, Glu), neutral amino acids (glycine, Tyr; D-threonine, Gly; tyrosine, Thr) and non-polar amino acids (D-alanine, Ala; valine, Val) in molar ratios of 1:5, 1:3, 1:1, 3:1 and 5:1, respectively. After mixing evenly, the mixture was preheated at 200°C for 20 minutes and then cooled to room temperature to measure its bonding strength.

[0065] Depend on Figures 17-20 It can be seen that the bonding strength of the adhesive made by compounding basic amino acids with dihydroxy ionic liquid IL1-1 is the highest, among which arginine has the highest bonding strength, up to 4.385MPa. The bonding strength of the adhesive made by acidic amino acids, neutral amino acids and non-polar amino acids with dihydroxy ionic liquid IL1-1 is generally low, among which aspartic acid among acidic amino acids has the highest bonding strength, which can reach 1.019MPa; tyrosine among neutral amino acids has the highest bonding strength, which can reach 0.340MPa, and valine among non-polar amino acids has the highest bonding strength, which can reach 0.593MPa, which meets the conventional interface bonding. The results show that the bonding strength of the adhesive made by most amino acids and dihydroxy ionic liquid IL1-1 reaches the maximum when the molar ratio of dihydroxy ionic liquid to amino acid is 1:3.

[0066] Example 10

[0067] The dihydroxy ionic liquid IL1-1 was ground and mixed with three guanidine-containing polymers with a large number of guanidine groups, namely polyhexamethylene biguanide hydrochloride, poly (hexamethylene dicyanoguanidine-hexamethylenediamine) hydrochloride and polyhexamethyleneguanidine hydrochloride, in molar ratios of 1:5, 1:3, 1:1, 3:1 and 5:1, respectively. After mixing evenly, the mixture was preheated at 200°C for 20 minutes, cooled to room temperature, and its bonding strength was measured.

[0068] The experimental results are as follows Fig.21 As shown, Poly.A represents polyhexamethylene biguanide hydrochloride, Poly.B represents polyhexamethylene guanidine hydrochloride, and Poly.C represents poly (hexamethylene dicyanamide-hexamethylene diamine) hydrochloride. It can be seen that the bonding strength of the three adhesives is relatively high, wherein the polyhexamethylene biguanide hydrochloride reaches a maximum of 10.992 MPa when the molar ratio is 1:1, the polyhexamethylene guanidine hydrochloride reaches a maximum of 7.186 MPa when the molar ratio is 1:3, and the poly (hexamethylene dicyanamide-hexamethylene diamine) hydrochloride reaches a maximum of 9.172 MPa when the molar ratio is 1:1. This shows that guanidine-containing polymers and dihydroxy ionic liquids can form adhesives with relatively high bonding strength.

[0069] In order to accurately test the bonding strength of the adhesive of the present invention, the sample interface bonding process includes the following steps: Taking the stainless steel substrate as an example, the substrate surface is cleaned before preparing the sample. To ensure the repeatability of the bonding strength, the stainless steel substrate is polished with 600-1000 grit sandpaper. The shear strength is tested using a single lap joint method, and the bonding area is 200mm 2 . The substrate is 200mm 2 100 mg of adhesive was evenly coated on the surface, and the temperature was set to preheat for 20 minutes. After the interface was completely wetted, the bonding areas of the two substrates were overlapped while hot, and 1 to 5 kg of pressure was applied to ensure that the bonding area was completely tight. 1 to 5 kg of pressure was applied to cool at room temperature to complete the interface bonding. The interface bonding test was completed using a universal material testing machine (WDW-100M, Jinan Zhongluchang Testing Machine Company), and the test method was based on the national standard GB / T 712-1986 single lap shear mode. Load in opposite directions at a shear rate of 20 mm / min until the lap shear specimen is separated or broken. The highest point in the shear force-displacement curve is the peak force at which the shear specimen is destroyed, that is, the maximum interface adhesion. According to the measured bonding area, the adhesive shear tensile strength can be calculated according to formula (1). Each group of shear tests was tested 7 times, and the average value was taken after removing the highest and lowest points.

[0070] τ = P / B·L (1)

[0071] Where: τ is the shear tensile strength of the adhesive, unit: MPa; P is the interfacial adhesion, unit: N; B is the width of the lap joint of the specimen, unit: mm; L is the length of the lap joint of the specimen, unit: mm.

[0072] According to the above steps, use adhesives P1~P4, PA~PD to bond 200mm 2 For samples made of 304 stainless steel, the bonding strength and average bonding strength of the five tests are shown in Tables 1 and 2.

[0073] Table 1 Adhesion strength of adhesives P1-P4 to 304 stainless steel substrate (MPa)

[0074]

[0075]

[0076] It can be seen from Table 1 that after different dihydroxy ionic liquids are mixed with arginine, under the condition of a certain molar ratio, the bonding strength is P3>P1>P4>P2.

[0077] Table 2 Adhesion strength of adhesives PA~PD to 304 stainless steel substrate (MPa)

[0078] Adhesives PA PB PC PD Test value 1 9.96 2.935 9.865 8.120 Test value 2 10.115 2.950 10.410 9.630 Test value 3 9.865 3.085 11.025 9.760 Test value 2 9.235 2.890 9.990 8.970 Test value 3 10.245 2.880 10.965 7.675 average value 9.884 2.948 10.451 8.831 Relative mean deviation 0.39084 0.08205 0.53649 0.91687

[0079] It can be seen from Table 2 that after different dihydroxy ionic liquids are mixed with guanidine-containing polymers (lysozyme), under the condition of a certain molar ratio, the order of adhesive strength is PC>PA>PD>PB.

[0080] The stainless steel sheets bonded with the adhesive PA were taken out after being immersed in different organic solvents (ethanol, dimethyl sulfoxide, methanol, dimethylformamide, petroleum ether, ethyl acetate, acetone, acetonitrile, ether, and dichloromethane) for 30 days, and their bonding strengths were measured. The results are shown in Table 3.

[0081] Table 3 Resistance of adhesive PA in different organic solvents

[0082]

[0083]

[0084] As can be seen from Table 3, after being placed in different organic solvents for 30 days, the bonding strength of adhesive PA has decreased to varying degrees. Among them, the tolerance to ethanol, petroleum ether and acetone is relatively good, and the bonding strength after 30 days has decreased to 75.5%, 83.7% and 71.6% respectively. The tolerance to methanol, ethyl acetate and ether is relatively poor, and the bonding strength after 30 days has decreased to 17.8%, 32.5% and 33.0% respectively. This shows that adhesive PA has a certain tolerance to different organic solvents and can still exert its bonding properties in some environments containing organic solvents.

[0085] In general, the thermosensitive adhesive prepared by the present invention using dihydroxy ionic liquid and amino acid or guanidine derivative or guanidine-containing polymer has adjustable bonding strength, and tolerance can be adjusted as needed in an organic solvent environment. The raw materials are green and environmentally friendly, and it is an environmentally friendly adhesive that is expected to be used in different occasions.

Claims

1. A heat-induced super strong adhesive, characterized in that: The adhesive is prepared by uniformly mixing a dihydroxy ionic liquid with an amino acid or a guanidine derivative or a guanidine-containing polymer and then subjecting the mixture to heat treatment; The dihydroxy ionic liquid is any one of the following IL1 to IL4: In the formula, m is an integer from 1 to 10, n is an integer from 1 to 10, and R represents Any of Represents anion.

2. The heat-induced super strong adhesive according to claim 1, characterized in that: Said Selected from Cl - Br - ,I - 、NO3 - , [PF6] - , [BF4] - 、[Al2Cl7] - 、[AlCl4] - 、[(CF3SO2)2N] - , dioctyl sulfosuccinate ion, [CF3SO3] - , [CF3COO] - Any one of .

3. The heat-induced super strong adhesive according to claim 1, characterized in that: The amino acid is selected from any one of alanine, valine, leucine, isoleucine, methionine, aspartic acid, glutamic acid, cysteine, phenylalanine, tryptophan, lysine, histidine, glycine, threonine, tyrosine and arginine.

4. The heat-induced super strong adhesive according to claim 1, characterized in that: The guanidine derivative is selected from any one of guanidine sulfate, guanidine phosphate, phenformin, chlorhexidine, guanidine benzoic acid, guanidine propionic acid, dodecylguanidine bromide, guanidine tetrafluoroborate, and biguanidine tetrafluoroborate.

5. The heat-induced super strong adhesive according to claim 1, characterized in that: The guanidine-containing polymer is selected from any one of polyhexamethylene biguanidine hydrochloride, poly(hexamethylene dicyanoguanidine-hexamethylene diamine) hydrochloride, polyhexamethylene guanidine hydrochloride, polyhexene guanidine, guanidine-modified chitosan, guanidine-modified polyvinyl alcohol, polyvinyl dichloride guanidine salt, guanidine polyacrylamide, and lysozyme.

6. The heat-induced super strong adhesive according to claim 1, characterized in that: The molar ratio of the dihydroxy ionic liquid to the amino acid or the guanidine derivative or the guanidine-containing polymer is 1:5 to 5:

1.

7. The heat-induced super strong adhesive according to claim 1, characterized in that: The heat treatment temperature is 100-200° C., and the heat treatment time is 10-60 minutes.